An Econometric Rational Expectations Macroeconomic Model for Developing Countries with Capital Controls. (IMF Working Papers; Working Paper ;, 1990)
A small macroeconomic model based on familiar theoretical considerations is developed and estimated using data from 31 developing countries. Efficient estimation techniques are used to control for country heterogeneity under the assumption of rational expectations. The estimates and the test statistics suggest that the model could serve well as a framework for developing-country macroeconomic analysis. An interesting feature of the specification of the model is that it allows the hypothesis of capital mobility to be explicitly tested. The empirical analysis suggests that on average developing countries tend to exhibit a high degree of capital mobility.